Neurodegenerative Susceptibility During Maternal Nutritional Programing: Are Central and Peripheral Innate Immune Training Relevant? - Cárdenas-Tueme, Marcela; Montalvo-Martínez, Larisa; Maldonado-Ruiz, Roger; Camacho-Morales, Alberto; Reséndez-Pérez, Diana (Frontiers in Neuroscience, 2020)
Maternal overnutrition modulates body weight, development of metabolic failure and, potentially, neurodegenerative susceptibility in the offspring. Overnutrition sets a chronic pro-inflammatory profile that integrates peripheral and central immune activation nodes, damaging neuronal physiology and survival. Innate immune cells exposed to hypercaloric diets might experience trained immunity. Here, we address the role of maternal overnutrition as a trigger for central and peripheral immune training and its contribution to neurodegeneration and the molecular nodes implicated in the Nod-like receptor protein 3 (NLRP3) inflammasome pathway leading to immune training. We propose that maternal overnutrition leads to peripheral or central immune training that favor neurodegenerative susceptibility in the offspring.